The Formation of the Aretological Catalogue as a Literary Form in the Greek Literature of Antiquity: from Homer to the New Testament - Левко, Олександр (Київський національний університет імені Тараса Шевченка, 2026)
Background. This article investigates the formation and functioning of aretological (ethical) catalogues in Ancient Greek, Hellenistic Jewish, and Early Christian literature. Ethical catalogues are treated as a component of the “discourse of virtues.” The aim of the article is to trace the genesis and development of the aretological catalogue from the archaic Greek tradition to the New Testament, to identify its rhetorical, stylistic, and didactic functions, and to demonstrate the interaction between Greek philosophical, Jewish, and Christian ethical models in New Testament texts. Methods. The study is based on an interdisciplinary approach combining literary and linguistic methods with biblical hermeneutics. It employs comparative, contrastive, and narratological methods, as well as contextual, stylistic, semantic, pragmatic, and intertextual analysis. Results. It is shown that the catalogue form emerges already in Ancient Greek epic and drama as a means of typification and rhetorical intensification, and that in the classical period, in the form of lists of virtues, it becomes integrated into philosophical discourse, particularly in the works of Plato and Aristotle. In the Hellenistic period, aretological catalogues become an autonomous didactic instrument, closely connected with Stoic ethics and epideictic rhetoric, and enter the Hellenistic Jewish tradition (Wisdom of Solomon, Philo of Alexandria). In the Bible and the New Testament, they function as a key device of moral paraenesis and codify models of desirable and undesirable behavior. Semantic changes in the names of virtues and vices in Hellenistic Jewish and Early Christian texts are identified, and the evolution of their meanings within aretological catalogues is traced. The article also presents, for the first time in Ukrainian, fragments of Hellenistic Jewish ethical discourse (Philo of Alexandria). Conclusions. Aretological catalogues are formed as a literary genre through the dialogue of different cultures: Greek, Jewish, and Early Christian. Among their main discursive functions are the suggestive, didactic, rhetorical, and epideictic functions. Further research prospects include the study of semantic and cultural transformations of ethical concepts in translations of classical and biblical texts into Latin and modern, particularly Slavic, languages, and their influence on the formation of ethical lexicons in modern languages.

Вступ. Статтю присвячено дослідженню становлення та функціонування аретологічних (етичних) каталогів у грекомовній античній, елліністично-юдейській та ранньохристиянській літературі. Етичні каталоги розглядаються як складник "дискурсу чеснот". Мета статті – простежити генезу й розвиток аретологічного каталогу від архаїчної грецької традиції до Нового Завіту, виявити його риторичні, стилістичні та дидактичні функції, а також показати взаємодію грецької філософської, юдейської та християнської етичних моделей у текстах Нового Завіту. Методи. Дослідження спирається на міждисциплінарний підхід і поєднує літературознавчі та лінгвістичні методи із залученням підходів біблійної герменевтики: зіставний, компаративний, наратологічний методи, методи контекстуального, стилістичного, семантичного, лінгвопрагматичного та інтертекстуального аналізу. Результати. Встановлено, що форма каталогу виникає ще в давньогрецькому епосі та драмі як засіб типізації й риторичної інтенсифікації, а в класичну добу у вигляді переліків чеснот інтегрується у філософський дискурс, зокрема твори Платона й Арістотеля. За доби еллінізму аретологічні каталоги стають автономним дидактичним інструментом, тісно пов’язаним зі стоїчною етикою та епідейктичною риторикою, і входять до елліністично-юдейської традиції (Книга Мудрості Соломона, Філон Александрійський). У Біблії та Новому Завіті вони функціонують як ключовий інструмент моральної паренези та кодифікують моделі бажаної та небажаної поведінки. У статті виявлено семантичні зміни в номінаціях античних чеснот і вад в елліністично-юдейських та ранньохристиянських текстах, простежено еволюцію семантики номінацій в аретологічних каталогах. Уперше подано фрагменти елліністично-юдейського етичного дискурсу українською мовою (Філон Александрійський). Висновки. Аретологічні каталоги формуються як літературна форма в результаті діалогу різних лінгвокультур: грецької, юдейської та ранньохристиянської. Серед основних дискурсивних функцій етичних каталогів можна виділити сугестивно-дидактичну, риторичну та епідейктичну. Перспективи дослідження полягають у вивченні семантичних і культурних трансформацій етичних понять у перекладах античних і біблійних текстів латинською та сучасними, зокрема слов’янськими, мовами, їх впливу на формування етичних лексиконів сучасних мов.
Становлення форми аретологічного каталогу в грекомовній літературі античності: від Гомера до Нового Завіту
Keywords: aretology; discourse of virtues; virtues and vices; Aristotle; Philo of Alexandria; Septuagint; New Testament; semantic change; аретологія; дискурс чеснот; чесноти і вади; Арістотель; Філон Александрійський; Септуагінта; Новий Завіт; семантичні зміни